Nonlinear effects of GDP regimes, renewable energy, and urbanization on Finland’s ecological footprint: An MT-NARDL approach - Irina Georgescu; Jani Kinnunen (World Development Sustainability, 2025)
This study employs the MT-NARDL framework to analyze Finland’s ecological footprint across GDP regimes, renewable and nuclear energy use, and urbanization. Findings confirm a nonlinear GDP-environment relationship: low GDP growth worsens ecological pressure, moderate growth offers temporary relief, and high GDP reduces impact, supporting the EKC hypothesis. Renewable energy initially raises ecological costs but proves beneficial long-term. Nuclear energy increases footprint due to waste concerns, while urbanization significantly amplifies environmental stress. Policy recommendations emphasize balancing economic growth with sustainability, optimizing renewable energy efficiency, improving nuclear waste management, and advancing sustainable urban planning.